Alumina‐based filters made via binder jet 3D printing of alumina powder, colloidal silica infiltration, and sintering. Issue 6 (19th August 2021) - Cramer, Corson L.; Armstrong, Beth L.; Trofimov, Artem A.; Wang, Peter L.; Siddel, Derek H.; Wang, Hsin; Cakmak, Ercan; Klett, James W.; Elliott, Amy M.
Abstract: Alumina‐based, porous filter media was made via a binder jet 3D printing process consisting of an alumina powder printing step with subsequent heating, colloidal silica infiltration, drying, and sintering to consolidate particles yet retain a net open porous microstructure. The composites made were alumina‐silica or alumina‐mullite, where the silica sintering aid was used to densify and join the alumina particles. The resulting composite structures had open porosities in the 25–31 vol% range as measured by Archimedes density. Pressure drops were measured across the filter media at constant flow rates to compare disc shapes and complex, 3D printed filters based on the N95 design requirements. Complex, 3D‐printed alumina composites were produced with acceptable pressure drops for N95 implementation.